STRATEGIC DETACHMENT AND LEADERSHIP REFUSAL: AN ANALYSIS OF MILLENNIALS AND GENERATION Z IN THE LABOR MARKET - Ferreira de Souza , Adriely; Paulo Festucci, João; Elaine Benetelli Geron, Regina (Revista Gênero e Interdisciplinaridade, 2025)
This article presents an in-depth analysis of the strategic distancing of Millennials and Generation Z members from formal leadership positions. The qualitative, exploratory, and bibliographical study reviews how historical transformations, technological advancements, cultural changes, and new perceptions of mental health and professional purpose are reshaping these generations' relationship with leadership roles. Drawing on classic and contemporary authors, it identifies motivational factors, structural pressures, and personal values ​​that underlie the refusal to assume traditional hierarchical positions. The results indicate that this retreat does not represent a lack of ambition, but a search for ethical coherence, work-life balance, and autonomy. The study also discusses how organizations can adapt to this new scenario by adopting collaborative and distributed leadership models.